THE ROLE OF AUDIOBOOKS IN LANGUAGE LEARNING - Norboyeva Zukhra Alijon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Learning methods are changing dramatically as a result of the rapid advancement  of  technology.  As  digital  technologies,  the  internet,  and  mobile applications have grown in popularity, alternative learning tools such as audiobooks have  become  more  popular.  Research  has  shown  that  using  audio  materials  can facilitate  better  language  learning  outcomes,  and  this  paper  examines  the  role  of audiobooks in language acquisition, their historical development, and their impact on contemporary learning approaches. Audiobooks are particularly effective in language learning  because  they  improve pronunciation, vocabulary  acquisition, and listening comprehension skills.